Gender Discrimination Among Academic Physicians - Chow, Candace J. (Womens Health Rep (New Rochelle), 2020)
Background: There is a growing body of literature showing that gender discrimination impacts physicians' work and life experiences. Impact on income, promotion, and parenthood has been documented. Based on these findings, we hypothesized that the experiences of academic physicians who identify as women or gender nonconforming would be different from their counterparts who are men. This survey study explores the influences of gender on academic physicians' experiences with discrimination in life and at work. Materials and Methods: In the spring of 2017, academic physicians (n = 752) at a medical school in the West were invited to participate in a survey that measured experiences with discrimination using the Everyday Discrimination Scale and additional items. We used a mixed-methods approach to analyze the data, employing chi square and t-tests to analyze quantitative data and modified content analysis to code open-ended responses. Results: The response rate was 24% (180/752). There was no significant difference between women and men in reported frequency of discrimination in everyday life (p = 0.474). However, women were significantly more likely than men to select gender as a reason for being treated differently in everyday life (p = 0.000) and report discrimination in the workplace (p < 0.000). Open-ended responses describing experiences of discrimination differed based on gender: women were twice as likely than men to report receiving negative treatment owing to gender. Finally, men discussed having gender privilege, whereas women discussed experiencing gender discrimination. Conclusions: This study contributes to the growing body of literature about how gender influences the experience of practicing medicine.